Aerosol characterization at the Saharan AERONET site Tamanrasset - C. Guirado; E. Cuevas; V. E. Cachorro; C. Toledano; S. Alonso-Pérez; J. J. Bustos; S. Basart; P. M. Romero; C. Camino; M. Mimouni; L. Zeudmi; P. Goloub; et al. (Atmospheric Chemistry and Physics, 2014)
More than 2 years of columnar atmospheric aerosol measurements (2006–2009) at the Tamanrasset site (22.79° N, 5.53° E, 1377 m a.s.l.), in the heart of the Sahara, are analysed. Aerosol Robotic Network (AERONET) level 2.0 data were used. The KCICLO (K is the name of a constant and ciclo means cycle in Spanish) method was applied to a part of the level 1.5 data series to improve the quality of the results. The annual variability of aerosol optical depth (AOD) and Ångström exponent (AE) has been found to be strongly linked to the convective boundary layer (CBL) thermodynamic features. The dry-cool season (autumn and winter) is characterized by a shallow CBL and very low mean turbidity (AOD ~ 0.09 at 440 nm, AE ~ 0.62). The wet-hot season (spring and summer) is dominated by high turbidity of coarse dust particles (AE ~ 0.28, AOD ~ 0.39 at 440 nm) and a deep CBL. The aerosol-type characterization shows desert mineral dust as the prevailing aerosol. Both pure Saharan dust and very clear sky conditions are observed depending on the season. However, several case studies indicate an anthropogenic fine mode contribution from the industrial areas in Libya and Algeria. The concentration weighted trajectory (CWT) source apportionment method was used to identify potential sources of air masses arriving at Tamanrasset at several heights for each season. Microphysical and optical properties and precipitable water vapour were also investigated.